CFD Simulation of Petcoke Gasification in an Updraft Gasifier - Ching, D.L.C. (Springer Science and Business Media B.V., 2021)
Gasification is an environmentally benign solution for producing energy from industrial wastes like petcoke. This can be done by partial combustion of petcoke within a fluidized bed gasifier (FBG). Since the fabrication of gasifier reactor is costly and time-consuming, the use of a reliable numerical technique reduces these extra costs significantly. Computational fluid dynamics (CFD) is a powerful tool to accurately validate the reactor design. In this study, CFD is used to predict the syngas composition of the petcoke gasification. It is found out that CFD model can predict well the syngas composition. Â© 2021, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.